2020
DOI: 10.1128/jvi.00901-20
|View full text |Cite
|
Sign up to set email alerts
|

Specific Akt Family Members Impair Stress-Mediated Transactivation of Viral Promoters and Enhance Neuronal Differentiation: Important Functions for Maintaining Latency

Abstract: Neurotropic α-herpesvirinae subfamily members, bovine herpesvirus 1 (BoHV-1) and herpes simplex virus type 1 (HSV-1) for example, establish and maintain life-long latent infections in neurons. Following infection of ocular, oral, or nasal cavities, sensory neurons within trigeminal ganglia (TG) are an important site for latency. Certain external stressors can trigger reactivation from latency, in part, because activation of the glucocorticoid receptor (GR) stimulates productive infection and promoters that dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 93 publications
2
7
0
Order By: Relevance
“…Two consensus GR response elements (GRE) in the IEtu1 promoter are essential for GR-α and DEX-mediated transactivation. Furthermore, the mouse mammary tumor virus LTR is strongly transactivated by DEX and GR-α expression plasmids in Neuro-2A [65], which is consistent with independent studies [69]. Hence, we believe transactivation of the ICP27 enhancer fragments by GR-α and KLF15 does not require DEX in Neuro-2A cells and only has a modest effect in CV-1 cells.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Two consensus GR response elements (GRE) in the IEtu1 promoter are essential for GR-α and DEX-mediated transactivation. Furthermore, the mouse mammary tumor virus LTR is strongly transactivated by DEX and GR-α expression plasmids in Neuro-2A [65], which is consistent with independent studies [69]. Hence, we believe transactivation of the ICP27 enhancer fragments by GR-α and KLF15 does not require DEX in Neuro-2A cells and only has a modest effect in CV-1 cells.…”
Section: Discussionsupporting
confidence: 90%
“…The effects of retinoic acid (RA) on these treatments were also examined, because reducing FBS and retinoic acid consistently arrests the cell cycle and establishes a neuronal-like phenotype in Neuro-2A cells, as denoted by neurite formation [59,62]. Consistent with our previous studies [63][64][65][66], incubating Neuro-2A cells in 2% stripped FBS for 48 h stimulated neurite formation (Figure 4A), which was enhanced by RA treatment. Although Neurobasal™ and a B-27 supplement are generally used for primary rodent neurons, its effects were examined in Neuro-2A cells.…”
Section: Influence Of Neurite Formation In Neuro-2a Cells On Icp27 Enhancer Activitysupporting
confidence: 76%
“…However, in vitro infection models using cultured primary neurons isolated from dissociated ganglia of rodents (Wilcox & Johnson, 1988; Camarena et al , 2010; Cliffe et al , 2015) recapitulate many aspects of in vivo animal models and provide a powerful opportunity to dissect the molecular circuitry that impacts virus‐neuron interactions and latency. Importantly, studies from our group and others have discovered that continuous neuronal host‐cell signalling through the AKT‐mTORC1 axis is required to maintain HSV‐1 latency (Camarena et al , 2010; Kobayashi et al , 2012; Hu et al , 2019; Zhao et al , 2020). Using this in vitro infection model, we recently showed that maintenance of HSV‐1 latency in primary neurons involves a convergence of the extrinsic TrkA receptor–mediated neurotrophin signalling with a secondary intrinsic signal generated via the endogenous nuclear DNA damage response (DDR) that acts together to maintain AKT activation (Hu et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…While it was clear that wt β-catenin did not significantly reduce IEtu1 promoter activity, we suggest that when the β-catenin destruction complex is not active, β-catenin directly or indirectly can impair certain promoters stimulated by stress. A recent study demonstrated that the serine/threonine protein kinase (Akt) impairs stress-induced transcription [ 55 ]. Since the Akt pathways and Wnt/β-catenin signaling pathways form a feed-forward signaling loop [ 56 , 57 , 58 ], we predict that the ability of β-catenin (S33Y) to impair stress-induced transcription is dependent on the Akt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%